Investors' perspective on portfolio insurance : expected utility vs prospect theories - Gaspar, Raquel M. (2019)
This study supports the use of behavioural finance to explain the popularity of portfolio insurance. Portfolio insurance strategies are important financial solutions sold to institutional and individual investors, that protect against downside risk while maintaining some upside valuation potential. The way some of these strategies are engineered has been criticised, and portfolio insurance itself blamed for increasing market volatility in depressed markets. Despite this, investors keep on buying portfolio insurance that has a solid market share. This study contributes to understand the phenomenon. We compare investors' decision using two distinct frameworks: expected utility theory and behavioural theories. Based upon Monte Carlo simulation techniques we compare portfolio insurance strategies against uninsured basic benchmark strategies. We conclude that cumulative prospect theory may be a viable framework to explain the popularity of portfolio insurance. However, among portfolio insurance strategies, naïve strategies seem to be preferable to most commonly traded strategies.